Surgical hand preparation metode handscrub dan handrub berbasis antiseptik: A scoping review - Olivia, Claudia; Ibrahim, Kusman; Kurniawan, Titis (Holistik Jurnal Kesehatan, 2025)
Background: Healthcare-associated infections (HAIs) are complications of healthcare that can increase morbidity, mortality, length of hospitalization, and additional costs, including surgical site infections (SSIs) caused by various factors such as microorganisms from the surgical environment. One important step in preventing SSIs is surgical hand preparation using antimicrobial soap or alcohol-based fluids which aims to reduce microorganisms, prevent infection, and increase the success of surgical procedures according to WHO and CDC guidelines. Purpose: To determine the effectiveness of implementing surgical hand preparation using antiseptic-based hand washing and hand rubbing methods. Method: Scoping review with article sources from PubMed, Scopus, and ScienceDirect published in the last 6 years in the period 2018-2024. The keywords used are "surgical team" or surgical staff or surgical procedures, "surgical hand preparation" or surgical cleaning or surgical rubbing, "bacteria" or microorganisms. Article assessment uses guidelines from The PRISMA Extension for Scooping Review (PRISMA-ScR). Results: The most widely used type of antiseptic fluid in the operating room area is chlorhexidine gluconate with concentrations of 1%, 3%, and 5% for the handrub method, and a concentration of 4% for the handwash-scrub method. The amount of antiseptic needed for handrub is 6-10 ml and for handwash-scrub 20 ml; and the surgical handwash and surgical handrub methods are equally effective in reducing the number of germs on the hands. Conclusion: Surgical handwash-scrub and surgical handrub are equally effective in reducing the number of bacteria on the hands, but surgical handrub with alcohol-based antiseptic and chlorhexidine is the main choice recommended by WHO and CDC because it is more practical, efficient, and effective than surgical handwash.   Keywords: Antiseptic; Handscrub; Handrub; Surgical Hand Preparation.   Pendahuluan: Health care–associated infections (HAIs) adalah komplikasi pelayanan kesehatan yang dapat meningkatkan morbiditas, mortalitas, durasi rawat inap, dan biaya tambahan, termasuk infeksi daerah operasi (IDO) yang disebabkan oleh berbagai faktor seperti mikroorganisme dari lingkungan operasi. Salah satu langkah penting dalam pencegahan IDO adalah persiapan tangan bedah menggunakan sabun antimikroba atau cairan berbasis alkohol yang bertujuan mengurangi mikroorganisme, mencegah infeksi, dan meningkatkan keberhasilan prosedur bedah sesuai pedoman WHO dan CDC. Tujuan: Untuk meyelidiki tentang efektivitas dari pelaksanaan surgical hand preparation metode handscrub dan handrub berbasis antiseptik. Metode: Scoping review dengan sumber artikel berasal dari pubMed, Scopus, dan ScienceDirect yang diterbitkan 6 tahun terakhir pada rentang 2018-2024. Kata kunci yang digunakan yaitu “surgical team” or surgical staff or surgical procedures, “surgical hand preparation” or surgical scrubbing or surgical rubbing, “bacteria” or microorganism. Penilaian artikel menggunakan panduan dari The PRISMA Extension for Scooping Review (PRISMA-ScR). Hasil: Jenis cairan antiseptik area kamar operasi yang paling banyak digunakan adalah chlorhexidine gluconate konsentrasi 1%, 3%, dan 5% untuk metode handrub, konsentrasi 4% untuk metode handwash-scrub. Jumlah antiseptik yang diperlukan untuk handrub 6-10 ml dan untuk handwash-brush 20 ml; dan metode surgical handwash dan surgical handrub sama-sama efektif dalam menurunkan jumlah kuman ditangan. Simpulan: Surgical handwash-scrub dan surgical handrub sama-sama efektif dalam menurunkan jumlah bakteri di tangan, tetapi surgical handrub dengan antiseptik berbasis alkohol dan chlorhexidine, menjadi pilihan utama yang direkomendasikan WHO dan CDC karena lebih praktis, efisien, dan efektif dibandingkan surgical handwash.   Kata Kunci: Antiseptik; Handscrub; Handrub; Surgical Hand Preparation.